Impact of Lead Exposure on Health, Nutritional Status, and Behavioral Problems among Children: A Comprehensive Review of Global Evidence - Shweta Naik; Komala M (CV. Doki Course and Training, 2026)
Lead (Pb) exposure remains a major environmental health threat affecting children worldwide. Although lead has been removed from gasoline, paints, and many industrial products, environmental contamination continues to expose millions of children. Due to their developing nervous systems and higher gastrointestinal absorption, children are especially vulnerable, and no safe level of lead exposure has been identified. This review synthesizes evidence published between 2000 and 2025 from PubMed, Scopus, Web of Science, ScienceDirect, Google Scholar, WHO, UNICEF, and government health reports. The findings indicate that lead exposure is strongly associated with impaired physical growth, nutritional deficiencies, reduced intelligence quotient (IQ), delayed neurodevelopment, poor academic performance, attention-deficit/hyperactivity disorder (ADHD), behavioural disorders, anaemia, stunting, and weakened immune function. Iron and calcium deficiencies further increase lead absorption and toxicity, while long-term exposure may contribute to mental health disorders and reduced productivity in adulthood. These findings highlight the need for integrated public health strategies, including environmental regulation, nutritional interventions, routine screening, community education, and stronger policy implementation to prevent childhood lead exposure and promote lifelong health.